Perception of Effort and Objective Levels of Intensity in Physical Education Classes of Primary Schoolchildren According to Gender and Nutritional Status: A Pilot Study - Mayorga Aguilar, Luis (2021)
This study focuses on the analysis of perceived effort and time of moderate and vigorous activities in physical education classes, considering differences based on gender and the nutritional status of schoolchildren. A total of 95 children in 5th and 6th grade of primary school in the city of Coyhaique, Chile, participated in the study. The EPInfant scale was used to assess the perceived effort, and Actigraph GT3X+ accelerometers were used to determine the time of moderate and vigorous activity. No significant differences were found in the perceived effort by gender (p=0.144); instead, by nutritional status, obese students indicated a higher perceived effort than students with a normal weight (p=0.220). Regarding moderate and vigorous activities in Physical Education class, the boys were significantly more active than the girls (p=0.017). In contrast, normal-weight children were slightly more active at this intensity level, but this difference was not statistically significant (p=0.622). The effort in Physical Education classes has been perceived as more demanding by the obese students; for this reason, it is important to understand the physical and motor difficulties that this group presents. Likewise, girls have participated for a shorter time in moderate and vigorous intensities, being pertinent to look for didactic strategies to increase the time of their participation.